(untitled) (Research, Society and Development, 2020)
Objective: to assess the knowledge of teachers and employees of a primary and secondary school, before and after an educational intervention on first aid. Method: quasi-experimental research with a single group, before and after type. The data were collected through a questionnaire, applied before and after the intervention. The sample consisted of 38 teachers and employees. Results: the average number of correct answers about knowledge in first aid increased from 11.13 to 19.45. There was a significant improvement in the participants’ knowledge regarding questions about breathing (p=0.001; p=0.004), cardiorespiratory arrest (p=<0.001; p=0.039; p=<0.001; p=<0.001), seizure crisis (p=< 0.001), fainting (p=<0.001), bleeding (p=<0.001; p=0.001; p=<0.001), choking (p=0.001), foreign body (p=<0.001) and fractures (p=<0.001). Conclusion: it is observed that there was an improvement in the level of knowledge of teachers and employees after the educational intervention, and the issues with greater significance when comparing the correct answers before and after the intervention were those related to breathing, cardiorespiratory arrest, seizure crisis, fainting, bleeding, choking, foreign body and fractures.